Understanding the evolution of superalloy microstructure during inertia friction welding using in-situ x-ray diffraction and cellular automata - Rowson, Matthew (2021)
The present work describes the development of a novel in-situ synchrotron diffraction technique for the characterisation of the microstructure evolution which occurs during IFW. These studies have quantified, for the first time, the spatial and temporal evolution of phase fractions which is produced by this process.